2022
DOI: 10.9734/ajacr/2022/v12i4226
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline Cellulose of Oil Bean Pod: Extraction, Physico-chemical, Brunauer–Emmett–Teller (BET), and Flow-ability Analysis

Abstract: Oil bean pods (OBPs) are a biomass that are indiscriminately dumped in eastern Nigeria, thus causes a lot of pollution. In this study, microcrystalline cellulose (MCC) was isolated from oil bean pods using acid hydrolysis, and several characterizations were performed using a variety of sophisticated techniques. Fourier transform infrared (FTIR) spectroscopy analysis has indicated the removal of lignin and hemicellulose from MCC extracted from oil bean pods. Scanning Electron Microscopy and Energy Dispersive X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Acetic acid with a larger volume caused a greater collision rate between molecules and led to more acetic acid molecules being present in the region of the starch [7]. Increases in DS make starch more hydrophobic, which makes it easier to mix with other polymers that are also hydrophobic [7,30]. These results concluded that C. bicolor starch has potential applications in the thermoplastic and polymer sectors.…”
Section: Percentage Of Acetyl Group and Degree Of Substitution (Ds)mentioning
confidence: 89%
See 1 more Smart Citation
“…Acetic acid with a larger volume caused a greater collision rate between molecules and led to more acetic acid molecules being present in the region of the starch [7]. Increases in DS make starch more hydrophobic, which makes it easier to mix with other polymers that are also hydrophobic [7,30]. These results concluded that C. bicolor starch has potential applications in the thermoplastic and polymer sectors.…”
Section: Percentage Of Acetyl Group and Degree Of Substitution (Ds)mentioning
confidence: 89%
“…The increase in the volume of acetic acid increases the gelatinization of acetylated starch. This implies that acetylated starch contains more amylose, which is strongly bound and requires higher energy to dissociate from their inner embedded core than the low amylose starches [29][30][31][32]. The lower gelatinization implies that the unmodified starch has less tightly bound amylase, and on heating releases this less bound amylose out of its inner core structure more easily, faster and with less energy.…”
Section: Gelatinization Temperature (Gt)mentioning
confidence: 99%
“…Additional clarification revealed that the peak corresponding to the -C=C-segment of a fatty acid was detected in SBF but was absent in SBF-polyol. This suggests that the process of converting Shea butter lipids into epoxides and hydroxides was successful, as the fatty acid component of Shea butter did not include any hydroxyl groups [2,32]. Both SBF and SBF-polyol showed the presence of peaks corresponding to the asymmetric or symmetric lengths of sp 3 (methyl) C-H, indicating the presence of methylene (CH2) groups as well as -C=O groups in RCHO and RCOOR.…”
Section: Discussionmentioning
confidence: 99%
“…The B and b were determined from the slope, whereas the AT was obtained from the intercept [46]. The heat of adsorption (B) less than 40 kJ/mol indicates a physical adsorption, and its value of more than 40 kJ/mol represents a chemical adsorption [14,44,46].The relationship between the adsorbents (modified and unmodified) and the metal ions (Cu(II) ion) was within the range of physical adsorption because the heat of adsorption was less than 40 kJ/mol. These findings corroborate the work of Saini et al [47], who investigated Cd(II) ion adsorption using unmodified and NTA-modified Dendrocalamus strictus charcoal powder.…”
Section: Langmuir Adsorption Isotherms Of Cu 2+ Celluloic-based Polym...mentioning
confidence: 99%
“…Some studies have used different traditional approaches to eliminate hazardous pollutants. Physical methods typically employed in this regard include ion exchange, filtration, membrane separation, evaporation, and reverse osmosis [13,14]. Both physical and chemical approaches demand a large initial investment and a high operating cost, and they are challenging to utilise in environments with low heavy metal concentrations [15,16].…”
Section: Introductionmentioning
confidence: 99%